Study on the Design and Implementation of BPPT-lock Armored Groin for Sediment Control Structure in Front of Sea Water Intake (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
High rate accumulation of sediment materials in front of the sea water intake (SWI) of a petrochemical factory cooling water system has caused high maintenance dredging costs. A study was conducted to identify the pattern and rate of sedimentation and to find an engineering solution that enables controlling sedimentation rate reduction. Based on numerical simulation, it is identified that the existing total rate of sedimentation around the channel in front of the SWI is 50cm/year. Further numerical simulation series revealed an optimum mitigation scenario by the construction of a pair of groin along both sides of the channel in front of the SWI as a sediment control structure. Under this scenario, the average bed level change becomes 0.10 cm/year and the maximum value of the bed level change is around 24.96 cm/year. A BPPT-lock armored rubble mound-type structure was designed for this sediment control groin by considering its feasibility, ease of construction, and local availability of structure materials. BPPT-lock is selected due to its high hydraulic stability (KD) of 17 for the trunk application and 13 for the head application. It is found that about twenty-five percent  more armor unit numbers were required at the final stage of construction compared to the designed one. The actual method of armor unit placement and arrangement during construction is considered the main cause of this difference. In this case, the calculation was designed for random placement, but the actual construction was in uniform placement. To provide economical insight, a calculation was made to compare the construction budget requirement between this constructed groin armored with BPPT-lock and if the same structure armored with tetrapod. The calculation result shows that BPPT-lock armor units required 64% less budget compared to the tetrapod.
Keywords: BPPT-lock, Budget, Design, Groin, Sediment control